VALUASI BISNIS PERUSAHAAN PT JAMINAN PEMBIAYAAN ASKRINDO SYARIAH DALAM RANGKA IPO DI TAHUN 2022 - Bunga Mareti Permatasari; Zulkifli Zulkifli; Syamsul Bahri (Gapenas Publisher, 2021)
In order to absorb the potential of the sharia guarantee business in the future which will grow rapidly, PT Jaminan Pembiayaan Askrindo Syariah with the brand name